Effects of the Short Foot Exercise With Neuromuscular Electrical Stimulation on Navicular Height in Flexible Flatfoot in Thailand: A Randomized Controlled Trial - Juntip Namsawang; Wichai Eungpinichpong; Ratana Vichiansiri; Somchai Rattanathongkom (Korean Society for Preventive Medicine, 2019)
Objectives Flatfoot, or low medial longitudinal arch, contributes to back and lower extremity injuries and is caused by weak abductor hallucis (AbdH) muscles. The purpose of this study was to investigate the effects of short foot exercise (SFE) alone or with neuromuscular electrical stimulation (NMES) on navicular height, the cross-sectional area (CSA) of the AbdH muscle, and AbdH muscle activity in flexible flatfoot. Methods Thirty-six otherwise healthy people with flexible flatfoot were randomly assigned to a group that received SFE with placebo NMES treatment (the control group) or a group that received both SFE and NMES treatment (the experimental group). Each group received 4 weeks of treatment (SFE alone or SFE with NMES). Navicular height, the CSA of the AbdH muscle, and AbdH muscle activity were assessed before and after the intervention. Results No significant differences were found in navicular height or the CSA of the AbdH muscle between the control and experimental groups, while AbdH muscle activity showed a statistically significant difference between the groups (SFE=73.9±11.0% of maximal voluntary isometric contraction [MVIC]; SFE with NMES=81.4±8.3% of MVIC; p<0.05). Moreover, the CSA of the AbdH muscle showed a statistically significant increase after treatment in the SFE with NMES group (pre-treatment=218.6±53.2 mm2; post-treatment=256.9±70.5 mm2; p<0.05). Conclusions SFE with NMES was more effective than SFE alone in increasing AbdH muscle activity. Therefore, SFE with NMES should be recommended to correct or prevent abnormalities in people with flexible flatfoot by a physiotherapist or medical care team.